Design, synthesis, and in silico evaluation of 1,4 dihydropyridine and 3,4 dihydropyrimidine 2(1H)-ones/thione derivatives - Manisha Ashwin Tayde; Suvarna Abhijeet Katti; Anuja Prabhakar Bhosale (Journal of Applied Pharmaceutical Research, 2026)
Background: Pyridine and pyrimidine derivatives occupy a central position in medicinal chemistry owing to their broad pharmacological significance. In particular, 1,4-dihydropyridines and 3,4-dihydropyrimidines are known for their anti-hypertensive and anti-anginal activities, encouraging further exploration of their chemical space. Methodology: This study aimed to design and synthesize a novel series of nineteen derivatives (PS-1 to PS-19) based on 1,4-dihydropyridine and 3,4-dihydropyrimidine-2(1H)-ones/thiones, employing a green synthetic strategy. The pharmacological viability of these compounds was assessed through in silico profiling. A catalyst-free "on-water" approach was used for synthesis, aligning with green chemistry principles to ensure eco-friendliness, operational simplicity, and high yield. Structural elucidation of the synthesized compounds was performed using infrared (IR) and proton nuclear magnetic resonance (^1H NMR) spectroscopy. Purity was assessed via thin-layer chromatography (TLC). Pharmacological activity, physicochemical properties, and toxicity profiles were evaluated using PASS Online, Swiss ADME, and Protox-II. Results and Discussion: Among the compounds screened, PS-4 demonstrated the most favorable docking affinity (−49.20), outperforming benchmark calcium channel blockers such as Nifedipine and Felodipine. The developed green synthetic method successfully yielded 19 target compounds with desirable purity and structural fidelity. Three compounds out of 19 showed a strong docking score towards the receptor protein. Conclusion: In silico results revealed favorable pharmacological potential and acceptable toxicity margins for several derivatives, suggesting they are promising candidates for further pharmacodynamic and therapeutic investigations.